2017
DOI: 10.3168/jds.2016-11605
|View full text |Cite
|
Sign up to set email alerts
|

The effects of elevated subcutaneous fat stores on fatty acid composition and gene expression of proinflammatory markers in periparturient dairy cows

Abstract: During the periparturient period, elevated circulating nonesterified fatty acids (NEFA) from excessive lipid mobilization affect not only the circulating fatty acid (FA) composition, but also that of the peripheral blood mononuclear cells (PBMC) and polymorphonuclear leukocytes (PMNL). However, the changes to specific lipid fractions remain unknown. We hypothesized that elevated lipid mobilization will alter FA profiles and gene expression of selected proinflammatory mediators in PBMC and PMNL. Starting -28 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…In order to compensate for the lack of energy, the body will mobilize lipids for decomposition; however, excessive lipid mobilization triggers a mass of free fatty acids to accumulate in the liver, resulting in fatty liver in postpartum dairy cows, with triglyceride accumulation impairing liver function and increasing pro-inflammatory responses [22]. In addition, excessive lipid mobilization also despoils the amount of inclusion of the leukocyte membrane, triggering the disruption of the membrane function of PBMC and PMN cells [23]. Additionally, impaired PBMC and PMN functions also increase susceptibility to disease in postpartum dairy cows [8].…”
Section: Discussionmentioning
confidence: 99%
“…In order to compensate for the lack of energy, the body will mobilize lipids for decomposition; however, excessive lipid mobilization triggers a mass of free fatty acids to accumulate in the liver, resulting in fatty liver in postpartum dairy cows, with triglyceride accumulation impairing liver function and increasing pro-inflammatory responses [22]. In addition, excessive lipid mobilization also despoils the amount of inclusion of the leukocyte membrane, triggering the disruption of the membrane function of PBMC and PMN cells [23]. Additionally, impaired PBMC and PMN functions also increase susceptibility to disease in postpartum dairy cows [8].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMC) were isolated, according to Scholte et al, [ 24 ] with modifications, from 50 mL of blood by gradient centrifugation using a mixture of Histopaque 1077 and 1119 (Sigma Aldrich, St. Louis, MO, USA). After centrifugation at 456× g for 1 h at room temperature, plasma was discarded, and the buffy coat and red blood cells were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Parity effects on gene expression regulation in PMNLs have seldom been reported in dairy cows. For instance, Scholte et al [56] observed an upregulation of genes related to inflammation (i.e., IL1B, IL6, and TNFA) and cell adhesion (ICAM) in primiparous cows in comparison to multiparous during the transition period. This suggests that younger animals have a more active immune response or better immunocompetence than older cows, where milk production might restrict nutrients to sustain a viable immune response.…”
Section: Gene Expressionmentioning
confidence: 99%